Service quality on use level of dental and oral health service at Puskesmas I Kemranjen - Kurnianda, Eva; Skripsa, Tira Hamdillah; Utami, Aras; Prabowo, Yoghi Bagus (BKM Public Health and Community Medicine, 2023)
Purpose: Along with the development of technology and the level of education, it is easy for the public to access information. With this, many people demand good quality health services, especially dental and oral health treatment, because customers pay attention to the result of the service. Good service quality can affect customer satisfaction and can support customers in using dental and oral services. Methods: This research was an observational analytic with a cross-sectional approach. This research was conducted at the work area of Puskesmas I Kemranjen from February to March 2022. The total sample was 179 respondents that met the inclusion criteria. The sampling technique used cluster random sampling. The instruments used in this research were the SERVQUAL service quality questionnaire and the service use level questionnaire. The statistical test used was a Spearman correlation test and continued with the ordinal logistic regression test. Results: The results of spearman correlation test analysis showed that there was a significant relationship between tangible (p < 0,001, r = 0,513), reliability (p < 0,001, r = 0,602), responsiveness (p < 0,001, r = 0,580), assurance (p < 0,001, r = 0,589), empathy (p < 0,001, r = 0,551) on the use level of dental and oral health services at Puskesmas I Kemranjen. The results of ordinal logistic regression analysis on the tangible dimensions obtained p = 0,024 and OR = 3,717; on the reliability dimension obtained p = 0,018 and OR = 4,508; on the responsiveness dimension obtained p = 0,003 and OR = 6,240; on the assurance dimension obtained p = 0,014 and OR = 3,962, on the empathy dimension p = 0,039 and OR = 3,320. Conclusion: According to the research results, there was a significant relationship between tangible, reliable, responsiveness, assurance, and empathy regarding the use level of dental and oral health services at Puskesmas I Kemranjen.